2012
DOI: 10.1021/mp3002232
|View full text |Cite
|
Sign up to set email alerts
|

Polyvalent Dendrimer-Methotrexate as a Folate Receptor-Targeted Cancer Therapeutic

Abstract: Our previous studies have demonstrated that a generation 5 dendrimer (G5) conjugated with both folic acid (FA) and methotrexate (MTX) has a higher chemotherapeutic index than MTX alone. Despite this, batch-to-batch inconsistencies in the number of FA and MTX molecules linked to each dendrimer led to conjugate batches with varying biological activity, especially when scaleup synthesis was attempted. Since the MTX is conjugated through an ester linkage, there were concerns that biological inconsistency could als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
163
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(174 citation statements)
references
References 47 publications
6
163
0
Order By: Relevance
“…Based on these results, it was suggested that although MTX has relatively lower affinity to folate receptor compared with FA (K D =~20-100 nM vs 31,32 MTX-conjugated micelles might bind to folate receptor through polyvalent interaction as reported recently. 21,33,34 cellular uptake mechanism of FITclabeled mixed micelles in KBv cells…”
mentioning
confidence: 99%
“…Based on these results, it was suggested that although MTX has relatively lower affinity to folate receptor compared with FA (K D =~20-100 nM vs 31,32 MTX-conjugated micelles might bind to folate receptor through polyvalent interaction as reported recently. 21,33,34 cellular uptake mechanism of FITclabeled mixed micelles in KBv cells…”
mentioning
confidence: 99%
“…Likewise, MTX does not exert its cytotoxic activity only towards neoplasic cells, but also targets other tissues, thus determining a range of side effects. Therefore, in order to overcome the undesirable toxicity of MTX and to circumvent the risks associated with the administration of the free drug, considerable research efforts have been directed toward novel nanotechnology-based MTX delivery approaches (Chen et al 2007;Kuznetsova et al 2012;Thomas et al 2012). Here, the enhanced cytotoxicity of MTX via the pH-responsive NPs means that a significant reverse effect of drug resistance could has occurred.…”
Section: In Vitro Assessments Of Antitumor Activitymentioning
confidence: 99%
“…This approach is paradoxical, as the synthesis of dendrimers aims at obtaining pure compounds, whereas the stochastic functionalization in the last step affords a mixture of compounds, which in particular can induce inconsistencies in biological responses [115].…”
Section: Dendritic Structures With Two Types Of Functions On Each Termentioning
confidence: 99%